Penghapusan Wilayah Kerja Pendidikan: Respon dan Implikasinya terhadap Kinerja Pengawas Satuan Pendidikan - Nuril Eka Fani Agustin; Iva Yulianti Umdatul Izzah (Jurnal Manajemen Publik dan Kebijakan Publik (JMPKP), 2026)
The Working Area, commonly referred to as Wilker, is a small unit located in each sub-district. Within the Working Area unit, there is a structure consisting of a regional coordinator (Korwil), staff, treasurer, and education unit supervisor. The existence of Wilker is considered important because it is geographically located in the area of the education unit supervisor's partner school, namely in each sub-district, thus facilitating the supervisor in providing guidance to schools. The policy to eliminate Wilker has created a new climate, requiring education unit supervisors to adapt and face challenges related to work mobility. This study uses a qualitative approach by interviewing representatives of supervisors, inspectors, and the Jombang District Education and Culture Office. This study aims to analyze the impact of the Wilker abolition policy on the performance of education supervisors in Jombang using symbolic interactionism theory as an analytical tool. The results of this study indicate that the elimination of Wilker received responses in the form of disappointment and negotiations regarding fingerprint rules, adaptation to digitization, and adjustments to coaching strategies, which were interpreted as symbolic changes in the work system that had implications for perceptions of effectiveness and the performance patterns of education unit supervisors